Sosialisasi Anak Dalam Keluarga Ibu Bekerja Di Lingkungan SMA Negeri 1 Belinyu - Johan; Fitri Ramdhani Harahap; Citra Asmara Indra (CV. Multi Kreasi Media, 2023)
The family serves as the primary socialization agent for a child, along with the environment that influences a child's growth and development. However, with an increasing number of mothers working outside the home, the role of mothers in child socialization has become more complex. This study aims to analyze how children are socialized in families where the mother works as a teacher. The research uses a qualitative method with a descriptive approach. Data were collected through in-depth interviews with working mothers and observations of family interactions. The results of the study show that there are distinct socialization patterns, namely the repressive and participatory socialization patterns. These patterns lead each family to have different methods of educating and nurturing their children. Additionally, the study also reveals that the time mothers spend outside the home can affect their interactions with their children. Limited time with children can result in fewer opportunities to impart social values and norms. This research provides a better understanding of how the role of working mothers as teachers influences child socialization within the family. The findings of this study are expected to contribute to future research and serve as a reference. Moreover, this research can offer insights for parents and families in managing interactions and socialization experiences for children in the context of the increasingly diverse modern family.